Pinpointing Drivers of Extirpation in Sea Snakes: A Synthesis of Evidence From Ashmore Reef - Somaweera, Ruchira; Udyawer, Vinay; Guinea, Michael L.; Ceccarelli, Daniela M.; Clarke, Rohan H.; Glover, Michelle; Hourston, Mathew; Keesing, John; Rasmussen, Arne Redsted; Sanders, Kate; Shine, Richard; Thomson, Damian P.; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.